2021
DOI: 10.5005/jp-journals-10006-1893
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Mifepristone with Dinoprostone Gel in Induction of Labor in Full-term Pregnancy: An Open-label Randomized Controlled Trial

Abstract: Aim and objective: This study aims to compare the effectiveness and safety of mifepristone with PGE2 gel for cervical ripening and induction of labor. Materials and methods:This was an open-label randomized controlled study; 191 patients were included and divided into 94 patients in group A (mifepristone) and 97 patients in group B (PGE2 gel). Tablet mifepristone 200 mg orally was given in group A, and intracervical PGE2 gel was given in group B. Preinduction Bishops score was noted at beginning to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(14 reference statements)
1
2
0
Order By: Relevance
“…We found that women who underwent outpatient cervical ripening with mifepristone had the same rate of Bishop score improvement as women in the inpatient group at 24 h (1 (1–2) vs. 1 (1–2), P = 0.416) and 48 h (3 (2–4) vs. 3 (1–4), P = 0.527). This Bishop score improvement was the same as or slightly lower than that reported in other studies [25] , [26] , [27] , [30] , [31] , [32] , [33] , [34] , [35] , [36] .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found that women who underwent outpatient cervical ripening with mifepristone had the same rate of Bishop score improvement as women in the inpatient group at 24 h (1 (1–2) vs. 1 (1–2), P = 0.416) and 48 h (3 (2–4) vs. 3 (1–4), P = 0.527). This Bishop score improvement was the same as or slightly lower than that reported in other studies [25] , [26] , [27] , [30] , [31] , [32] , [33] , [34] , [35] , [36] .…”
Section: Discussionsupporting
confidence: 86%
“…An additional advantage of the high degree of cervical ripening was the low rate of oxytocin use for labour induction (6.25 % and 12.96 %, respectively). We assume that this is the lowest rate among the available data (25–90 % in other studies) [19] , [24] , [30] , [31] , [33] , [36] .…”
Section: Discussionmentioning
confidence: 98%
“…It is the 19 norsteroid, which has greater affinity for progesterone receptor than progesterone itself. It blocks the action of progesterone at the cellular level [4] .…”
Section: Introductionmentioning
confidence: 99%